Pharmacological Inhibition of Protein Kinase G1 Enhances Bone Formation by Human Skeletal Stem Cells Through Activation of RhoA‐Akt Signaling. (23rd April 2015) - Jafari, Abbas; Siersbaek, Majken S.; Chen, Li; Qanie, Diyako; Zaher, Walid; Abdallah, Basem M.; Kassem, Moustapha
Abstract: Development of novel approaches to enhance bone regeneration is needed for efficient treatment of bone defects. Protein kinases play a key role in regulation of intracellular signal transduction pathways, and pharmacological targeting of protein kinases has led to development of novel treatments for several malignant and nonmalignant conditions. We screened a library of kinase inhibitors to identify small molecules that enhance bone formation by human skeletal (stromal or mesenchymal) stem cells (hMSC). We identified H‐8 (known to inhibit protein kinases A, C, and G) as a potent enhancer of ex vivo osteoblast (OB) differentiation of hMSC, in a stage‐ and cell type‐specific manner, without affecting adipogenesis or osteoclastogenesis. Furthermore, we showed that systemic administration of H‐8 enhances in vivo bone formation by hMSC, using a preclinical ectopic bone formation model in mice. Using functional screening of known H‐8 targets, we demonstrated that inhibition of protein kinase G1 (PRKG1) and consequent activation of RhoA‐Akt signaling is the main mechanism through which H‐8 enhances osteogenesis. Our studies revealed PRKG1 as a novel negative regulator of OB differentiation and suggest that pharmacological inhibition of PRKG1 in hMSC implanted at the site of bone defect can enhance bone regeneration. Stem Cells 2015;33:2219–2231